Jay's journal - Sparks, Beatrice (New York : Simon Pulse, 2010)
A withdrawn adolescent boy's initiation into the occult draws him ever deeper into the bizarre world of witchcraft, voodoo, and satanism until, at age sixteen, he commits suicide.
Originally published: New York : Times Books, c1979.
Keywords: Teenagers -- Suicidal behavior -- Fiction; Drug abuse -- Fiction; Magic -- Fiction